Problem based learning and involvement in off campus organization enhance studentsâ critical participation behavior (Faculty of Medicine Universitas Indonesia, 2009)
Aim Developing students’ critical thinking and critical participation in solving patients’ as well as a community’s problem should become the concern of medical education. This study aimed to identify several factors related to medical students’ critical participation behavior. Methods The subjects consisted of students of Sultan Agung Medical School (Unissula), year entry 2005, 2006, and 2007. Critical participation behavior was assessed using modified EMI: Critical Thinking Disposition Assessment. Relative risks (RR) were calculated using Cox regression analysis with constant time. Results 64,6% (388 out of 600) of the students participated in this study. Those who were involved in PBL for two and three years, rather than one year, had twice as high good critical thinking behavior [adjusted relative risk (RR) = 2.07; 95% confidence interval (CI) = 1.37–3.14; and RR = 2.33; 95% CI = 155–3.49, respectively.] Students who were more involved in off- campus organizations had a good critical participation behavior; 75% higher than those who were not involved in off-campus organizations (RR = 1.75; 95% CI = 0.99–3.11). Conclusion Besides involving in PBL learning approach, students should be motivated to be involved in off-campus organizations in order to improve their critical participation behavior (Med J Indones 2009;18:215-20)